Help-seeking behaviours related to mental health symptoms in professional football. Issue 2 (17th May 2021) - Confectioner, Kaizeen; Currie, Alan; Gabana, Nicolle; van Gerven, Nienke; Kerkhoffs, Gino M M J; Gouttebarge, Vincent
Abstract : Objectives: The primary objective was to examine the attitudes of professional footballers towards help-seeking behaviours related to mental health symptoms and the impact of a mental health awareness video on these help-seeking behaviours. The secondary objective was to evaluate whether the mental health awareness video was feasible in professional football. Methods: A quasi-experimental study based on a one-group pretest post-test was conducted using a questionnaire. Attitude, help-seeking behaviours and confidence were measured with validated questionnaires, including the Attitudes Toward Seeking Professional Psychological Help-Short Form (ATSPPH-SF) and General Help-Seeking Questionnaire (GHSQ). Results: Sixty-five professional footballers (63% men; 37% women) were enrolled in the study. The mean ATSPPH-SF score was 18.1 at pretest and 19.4 at post-test (p=0.00). The mean GHSQ score was 47.6 at pretest and 48.9 at post-test (p=0.00). The level of confidence in helping someone experiencing mental health symptoms was 11.1 at pretest and 11.7 at post-test (p=0.00). All participants rated the mental health awareness video as relevant; 88% mentioned that it added value to raise awareness about mental health symptoms and disorders in professional football. Eighty-three per cent rated the design positively, 69% were positive about the duration of the video and 88% of participants reported an increase in their knowledge and understanding of mental health symptoms and disorders in professional football. Conclusion: The mental health awareness video led to a better attitude of professional footballers towards mental health. We recommend the mental health awareness video be implemented in professional football to disseminate essential information related to mental health symptoms in professional football.